Kebijakan Hutang Dan Kepemilikan Manajerial Pada Nilai Perusahaan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017- 2021 - Lilis Marlina; Lidya Martha (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to determine the effect of debt policy (DER) and managerial ownership on the value of companies listed on the Indonesia Stock Exchange in 2017-2021. The year used in this study is five years, starting from 2017-2021. Samples were taken using purposive sampling method. The population in this study are all companies listed on the Indonesia Stock Exchange in 2017-2021. From a population of 810 companies listed on the Indonesia Stock Exchange, 45 companies were obtained as a sample with an observation period of five years (2017-2021). Data were analyzed using panel data regression. Based on the results of data analysis it was concluded that debt policy (DER) had a positive and significant effect on firm value with a t-value of 8.628708 and a significance of 0.000 so that the first hypothesis was accepted. Managerial ownership has a positive and significant effect on firm value with a t value of 2.28933 and a significance of 0.0230, so the second hypothesis is accepted.